Peran Lembaga Penyiaran Sebagai Sarana Komunikasi Politik dalam PILKADA Sulawesi Utara Tahun 2020 di Tengah Pandemi Covid-19 - Amisan, Pangasihan; Pioh, Novie Revlie; Pangemanan, Fanley N. (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
TV and Radio broadcasting institutions in their function as a means of mass communication, play an important role in disseminating credible information to the public in the 2020 North Sulawesi Governor and Deputy Governor elections. The Governor and Deputy Governor candidate pairs and their success teams also took advantage of this means to convey their political messages, in the form of visions and missions and work programs, and information on their track record of success along with invitations to vote. From the 2020 Pilkada news broadcasts and campaign advertisements such as those aired on LPP TVRI North Sulawesi Station, Kompas TV Manado, Kawanua TV, LPP RRI Manado, LPP RRI Tahuna and other mass media, the public gets enough information about the track record and ideas of the candidate pairs to be elected so that it becomes a consideration in making choices. Political messages containing invitations delivered by candidates for Governor and Deputy Governor indirectly influence the attitude of voters in making their choices. With this function, the media is able to supply the information needs of the audience. In political communication, the most realistic fact to be used as a measure of the success of message delivery is the increasing number of audiences who agree on what the content of the message is and more explicitly are willing to become followers of political communicators. With the opinion of the community as communicants or recipients of political messages, that their choice when voting is partly influenced by the message of the political communicator.